2017
DOI: 10.3390/molecules22050732
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis Extract Synergizes with Protoporphyrin IX-mediated Photodynamic Therapy via Enhancement of Intracellular Accumulation of Protoporphyrin IX and Attenuation of NF-κB and COX-2

Abstract: Brazilian green propolis (BGP) is noted for its impressive antitumor effects and has been used as a folk medicine in various cultures for many years. It has been demonstrated that BGP could enhance the cytotoxic effect of cytostatic drugs on tumor cells. Photodynamic therapy (PDT) is a therapeutic approach used against malignant cells. To assess the synergistic effect of BGP extract on protoporphyrin IX (PpIX)-mediated photocytotoxicity, MTT assays were performed using A431 and HeLa cells. TUNEL assay and Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…After blocking the membranes for 2 h at room temperature with 5% nonfat dried milk, membranes were incubated with primary antibody overnight at 4 °C. After incubation with secondary antibody for 2 h at room temperature, immunoreactive bands were visualized by Immobilon Western chemiluminescent HRP substrate (Millipore, Darmstadt, Germany) 62 . The following antibodies were used as primary antibodies in immunoblotting: AC-15 (mouse anti-human β-actin; Sigma-Aldrich), 3H2-E8 (mouse anti-Epstein-Barr Virus Blimp-1, Novus); 0211 (mouse anti-Epstein-Barr Virus EBNA-1, Santa Cruz), CS.1–4 (mouse anti-Epstein-Barr Virus LMP; DAKO), D84C12 (rabbit anti-c-Myc), 124H6 (mouse anti-human Stat3), M9C6 (mouse anti-human Phospho-Stat3 (Tyr705)), 9F6 (rabbit anti-human c-Fos), 60A8 (rabbit anti-human c-Jun), D52F9 (rabbit anti-human Cyclin D2), HE12 (mouse anti-human Cyclin E1), 4H1 (mouse anti-human Rb), and 9308 (rabbit anti-human Phospho-Rb (Ser807/811)) from Cell Signalling Technology.…”
Section: Methodsmentioning
confidence: 99%
“…After blocking the membranes for 2 h at room temperature with 5% nonfat dried milk, membranes were incubated with primary antibody overnight at 4 °C. After incubation with secondary antibody for 2 h at room temperature, immunoreactive bands were visualized by Immobilon Western chemiluminescent HRP substrate (Millipore, Darmstadt, Germany) 62 . The following antibodies were used as primary antibodies in immunoblotting: AC-15 (mouse anti-human β-actin; Sigma-Aldrich), 3H2-E8 (mouse anti-Epstein-Barr Virus Blimp-1, Novus); 0211 (mouse anti-Epstein-Barr Virus EBNA-1, Santa Cruz), CS.1–4 (mouse anti-Epstein-Barr Virus LMP; DAKO), D84C12 (rabbit anti-c-Myc), 124H6 (mouse anti-human Stat3), M9C6 (mouse anti-human Phospho-Stat3 (Tyr705)), 9F6 (rabbit anti-human c-Fos), 60A8 (rabbit anti-human c-Jun), D52F9 (rabbit anti-human Cyclin D2), HE12 (mouse anti-human Cyclin E1), 4H1 (mouse anti-human Rb), and 9308 (rabbit anti-human Phospho-Rb (Ser807/811)) from Cell Signalling Technology.…”
Section: Methodsmentioning
confidence: 99%
“…The Africanized bees of the Southeast region are able to produce propolis from buds of leaves of B. dracunculifolia not yet expanded, guaranteeing a product with high concentrations of phenols and Artepillin C (3,5-diprenyl-4-hydroxycinnamic acid), a compound only found in propolis in the Southeast region on Brazil. 12 In this way, caffeic ferulic, p- coumaric acids, kaempferol, kaempferide, and Artepillin C are the main constituents of the Brazilian green propolis. 13 Artepillin C presents several activities such as antioxidant, antimicrobial, anti-inflammatory, antigenotoxic, antiangiogenic, and anticancer properties.…”
Section: Review Methodsmentioning
confidence: 99%
“…Brazilian red propolis is obtained by bees from the species Apis mellifera mainly from the sap of Dalbergia ecastophyllum , which is a leguminous plant found in the northeastern mangroves of Brazil. 12 One of its botanical origin is a legume identified as D. ecastophyllum L., found in a region of tropical coastal climate, specifically the mangrove region. Its stem is reddish, so the product of propolis accompanies the coloration.…”
Section: Review Methodsmentioning
confidence: 99%
“…Thereafter, our group demonstrated that both the oil and hydroalcoholic extract of propolis elicits anxiolytic effects on an arena and elevated plus‐maze paradigm 13,20 . In the studies described above, CAPE and pinocembrin were absent in the propolis constituents; however, other phenolic hydroxyl group, including CA and its correlates, which have reported anxiolytic effects, were sometimes present 13,68,69 …”
Section: Neuropharmacological Effectsmentioning
confidence: 97%